Student Satisfaction and Perception of Performance in the E-Learning Environment during the Covid-19 Pandemic in Higher Education - Zulpikar, Zulpikar; Fatkhunnajah, Emmie (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Covid-19 as a global public health crisis has had an impact on the economy, education and food security of all people in the world, regardless of national boundaries. The sectors affected include tertiary education, which presented one of the barriers during the periodlockdownconsidering that most major countries have kept important economic activities running. The results of this study indicate that: student computer skills are correlated with home infrastructure, the quality of E-learning has a positive effect on student satisfaction, student satisfaction has a positive effect on student performance, and motivation in online classes has a positive effect on student learning perceptions.